PIPING AND INSTRUMENTATION DAIGRAM OF (P&ID) THERMAL POWER STATION - JANKAR, Mr. SUNIL; RATHORE, Prof. R S; GUPTA, ASHOK KUMAR (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
A P&ID is a detailed graphical representation of a process including the hardware and software (e.g., piping, equipment, instrumentation) necessary to design, construct and operate the facility as well as demonstrates all the piping with flow direction and instruments details with their controls. The equipments also show all the operational information at the top or bottom of the sheet. All the equipments and instruments including pipelines and values are tagged uniquely. P&IDs often look very complicate because they show so much information in single sheet so it is broken down into small parts and then after it is studied